Development and Performance Evaluation of a Novel Ancestry Informative DIP Panel for Continental Origin Inference - Zhou, Yongsong; Jin, Xiaoye; Wu, Buling; Zhu, Bofeng (Frontiers in Genetics, 2022)
Ancestry informative markers (AIMs) are genetic markers that display high genetic divergences between different populations. In recent years, forensic researchers have constructed a batch of AIM panels for forensic ancestry origin analyses. However, these extant panels are hard to differentiate Chinese populations, which might be related to limited genetic data of Chinese populations. In this study, we chose 52 ancestry informative deletion/insertion polymorphisms (AIDIPs) for ancestry origin analyses of different continental and Chinese populations. Genetic distributions of 50 AIDIPs in different continental populations revealed that most loci showed high genetic differentiation between East Asian populations and other continental populations. Population genetic analyses (principal component analysis and admixture) of different continental populations indicated that these 50 AIDIPs could discriminate East Asian, European and African populations. In addition, selected 52 AIDIPs exhibited relatively high cumulative discrimination power in Eastern Han population and could be used as a supplementary tool for forensic individual identification. What’s more, Eastern Han population showed close genetic relationships with East Asian populations and high ancestral components from East Asian populations. In the future, we need to investigate genetic distributions of these 52 AIDIPs in Chinese Han and other groups and evaluate the power of these loci to differentiate Chinese populations.